Phylogenetic origin of Magnolia pseudokobus (Magnoliaceae), a rare Magnolia extinct in the wild, revealed by chloroplast genome sequencing, genome-wide SNP genotyping and microsatellite analysis. Issue 5 (2nd September 2020) - Sakaguchi, Shota; Nagasawa, Koki; Umetsu, Yukie; Nagasawa, Jun-ichi; Ichikawa, San-ei; Kinoshita, Satoru; Hiratsuka, Ken-ichi; Suyama, Yoshihisa; Tsunamoto, Yoshihiro; Isagi, Yuji; Setoguchi, Hiroaki
ABSTRACT: The phylogenetic origin of endangered species extinct in the wild is not always well understood, as a consequence of limited historical records of the original populations. Magnolia pseudokobus (Magnoliaceae) is one of only a few such woody plants in Japan. This triploid species was described in 1954 on Shikoku Island, but since then, no other individuals have been found in other locations. Currently, the only genet clonally propagated from the original tree can be seen in botanic gardens. In this study, we aimed to phylogenetically position M. pseudokobus by investigating genetic variations in the chloroplast genome, genome-wide SNPs, and microsatellites of focal and related species. Phylogenetic trees based on the chloroplast genome and nuclear single nucleotide polymorphism (SNP) markers consistently showed that M. pseudokobus is well embedded within a clade consisting of M. kobus samples. Microsatellite analysis on a seedling of M. pseudokobus, which was cultivated adjacent to a M. kobus tree, showed that it was an interspecific hybrid. The genetic data suggest that M. pseudokobus was generated recently from M. kobus, allowing for the production of viable seedlings. Considering that the species is triploid and is not agamospermous, and any wild populations of M. kobus are not known from Shikoku Island, M. pseudokobus may be a ploidy variant of M. kobus, generated by spontaneous triploidization in M. kobus individual(s), which were possibly introduced by humans as ornamental tree(s). In conclusion, M. pseudokobus appears to be conspecific with M. kobus, and better recognized as M. kobus f. pseudokobus .